Efficacy and Safety of Xuebijing Injection, an Herbal-Based Injection, in Patients with Sepsis: Evidence from Randomized Controlled Trials of 3007 Subjects. - Cao, Gang; Liu, Liang; He, Xin; Wang, Rui; Liang, Bo (Journal of Integrative & Complementary Medicine, 2026)
Background: Xuebijing injection was approved for treating sepsis; however, the efficacy and safety of Xuebijing injection in population with sepsis need further evaluation. We aimed to evaluate the safety and efficacy of Xuebijing injection on sepsis. Materials and Methods: We searched for potential randomized controlled trials about Xuebijing injection and sepsis from six public databases. Primary outcomes included the 28-day mortality and mortality during treatment. Our secondary outcomes were body temperature, APACHE Ⅱ score, and adverse events or reactions. All data were synthesized by the meta package. Results: A total of 3007 patients (1551 patients receiving the conventional treatment combined with Xuebijing injection and 1456 patients receiving the conventional treatment only) were included. We found Xuebijing injection reduced the 28-day mortality (risk ratio = 0.69 [0.60–0.78], p < 0.0001), mortality during treatment (risk ratio = 0.74 [0.62–0.88], p = 0.0009), APACHE II score (mean difference = 3.91 [2.45–5.38], p < 0.0001), and body temperature (mean difference = 0.43 [0.31–0.55], p < 0.0001) without obvious adverse events (risk ratio = 0.91 [0.77–1.07], p = 0.2405). Conclusions: Xuebijing injection is effective and safe for treating sepsis. Additional methodologically sound trials with long-term mortality as an outcome measure could provide further insights into whether Xuebijing injection offers an enhanced therapeutic effect for sepsis.